Divulging Students’ Speaking Ability in Personal Branding Projects - Solusia, Carbiriena (UIR Press, 2025)
Speaking ability plays an important role in communicative competence. How well someone speak will determine how others will perceive their ability in English. Therefore, being able to present Personal Branding in the classroom will help students exercise how promote themselves once they join the job market after they graduate. Personal Branding project showcases students’ speaking ability. Their Grammar, Vocabulary, Pronunciation, Fluency, and Comprehension are carefully assessed using Brown’s speaking scoring rubric. There are small number of studies focusing on analyzing students’ speaking ability in Personal Branding. Besides, Personal Branding is a newly introduced project in Public Speaking Class at English Literature Class of English Department Universitas Negeri Padang. Consequently, there needs to be some analysis and review of this project in the classroom. This research utilized Descriptive Quantitative method with 23 students of English Literature as the sample. The results show that students’ Comprehension obtain the highest score with 4 out of 5 points, closely followed by Vocabulary and Fluency with 3,91 and 3,83 out of 5. Meanwhile, Grammar and Pronunciation followed last with an average score of 3,39 and 3,17 out of 5. This contrast suggests that although students demonstrate a strong understanding of meaning during speaking tasks, they experience greater difficulty in maintaining smooth and confident oral expression, revealing a gap between their comprehension and their ability to pronounce language well. For their overall score, all of the students passed the Personal Branding project with an average score of 73,22 out of 100. In conclusion, Personal Branding as a project can be implemented in the classroom with more pronunciation practices beforehand. Students’ ability in executing this project well also help them preparing their personal brand once they join the job market.